Processed Red Ginger (Zingiber Officinale Var Rubrum) into Instant Ginger as a Healthy Drink - Ruat Diana; I Putu Ayub Darmawan (Khaliya Onomiyea: Jurnal Abdimas Nusantara, 2023)
Processed ginger used to be limited as a spice but has now become a health drink. The purpose of this scientific work is to determine the process of making instant ginger with the basic ingredients of red ginger (Zingiber officinale). The method used is qualitative through library research. Data collection techniques through field observations. Literature research and the practice of making instant ginger. This paper provides research information on the health effects of red ginger immunity. The process of processing red ginger becomes instant in a simple way that can be done in the home industry. This instant ginger drink can help increase immunity for Covid-19 survivors and also maintain body health.